Anticancer Properties of Caulerpa racemosa: A Review Study. - PERMATASARI, Happy Kurnia; BULAIN, Stanley; AMAR, Nasim; AZIZAH, Maghfira Rahma; MUSLIM, Farida Zharfani; DAUD, Vanessa Pradna Adyana; NURKOLIS, Fahrul (Nutrición Clínica y Dietética Hospitalaria, 2022)
Introduction: Cancer is the leading cause of death in the world, with approximately 10 million deaths expected by 2020. Several approaches are used in cancer management. However, the cost is one of the main obstacles in cancer therapy as well as side effects in sufferers. Caulerpa racemosa is a type of seaweed that is naturally abundant in the Indonesian sea. Recently, there has been much research on the anticancer effects of Caulerpa sp. This study aims to find the potency of Sea grapes extract (Caulerpa racemosa) in the treatment of cancer and its mechanisms. Method: A review of the literature was constructed on the potential of the C. racemosa extract with the PICOS criteria and the data were extracted from ‘PUBMED’, ‘ScienceDirect’ and ‘SpringerLink’. The search method was using a boolean operator with the main keywords ‘Caulerpa racemosa’, ‘cancer’, and ‘Management’. Results: The main results were 8 articles including in vitro and in vivo experimental studies based on inclusion criteria. Several studies (n=8) revealed the potency of C. racemosa extract as an anticancer agent through various activities, such as antiproliferative, apoptotic, antioxidant, cytotoxic activity, and inhibition of tumor progression genes, DNMT, and upregulation of proapoptotic genes, including BAX, P53, Caspase-3, Caspase-8, and Caspase-9. Discussion: C. racemosa possesses several potent antioxidant substances, along with gene regulation activities and in hibition of cell line proliferation. Seaweeds has been used widely as functional food and showed minimal or no toxicities against human. With all these benefits, C. racemosa has the potential to be commercialized as a promising diet for cancer patients. Conclusion: Sea grapes extract (C. racemosa) has good potential as an anticancer agent through antiproliferation mechanisms, induction of apoptosis, cytotoxic and antioxidant activity.